2011
DOI: 10.1038/onc.2011.491
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the candidate tumor suppressor BTG3 triggers acute cellular senescence via the ERK–JMJD3–p16INK4a signaling axis

Abstract: The B-cell translocation gene 3 (BTG3) is a member of the antiproliferative BTG gene family and a downstream target of p53. BTG3 also binds and inhibits E2F1. Although it connects functionally two major growth-regulatory pathways, the physiological role of BTG3 remains largely uncharacterized. Here, we present evidence that loss of BTG3 in normal cells induced cellular senescence, which was correlated with enhanced ERK-AP1 signaling and elevated expression of the histone H3K27me3 demethylase JMJD3/KDM6B, leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 26 publications
3
44
0
Order By: Relevance
“…As follows, its physiological functions began to be discovered, such as neuron phylogenesis, the control of muscle cell development and bone formation (Putnik et al 2012), especially, for the control of cell cycle (Winkler 2010;Lim 2006;Yamamoto et al 2001;Lin et al 2012). Recently, several studies have shown that BTG3 was associated with tumorigenesis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As follows, its physiological functions began to be discovered, such as neuron phylogenesis, the control of muscle cell development and bone formation (Putnik et al 2012), especially, for the control of cell cycle (Winkler 2010;Lim 2006;Yamamoto et al 2001;Lin et al 2012). Recently, several studies have shown that BTG3 was associated with tumorigenesis.…”
Section: Discussionmentioning
confidence: 97%
“…The expression of BTG3 is down-regulated in lung adenocarcinoma, oral squamous cell cancer or prostate cancer (Yoneda et al 2009;Yamamoto et al 2001;Lin et al 2012). Aberrant epigenetic regulation of BTG3 promoter, such as by DNA hypermethylation and/or histone modification, is observed in several human cancers (Majid et al 2009(Majid et al , 2010Yu et al 2008;Putnik et al 2012).…”
mentioning
confidence: 97%
“…Recent researches demonstrate that the family could inhibit cell proliferation and regulate cell-cycle progression and differentiation in a variety of cell types [26, 27]. At present, numerous studies have demonstrated that BTG3 plays a suppressive role in cancer progression and the down-expression of BTG3 could lead to the development of gastric cancer, lung cancer, esophageal adenocarcinoma, and prostate cancer [28-31]. All these results suggest that BTG3 might function as a tumor suppressor in many systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence has demonstrated that BTG3 functions as a tumor suppressor in cancer progression. BTG3 expression is downregulated in lung adenocarcinoma, oral squamous cell cancer, or prostate cancer [19][20][21][22]. It was reported that BTG3 was a suppressor in the ESC progression [4].…”
Section: Discussionmentioning
confidence: 98%